Contributions of Stepping Intensity and Variability to Mobility in Individuals Poststroke: A Randomized Clinical Trial. Issue 9 (September 2019) - Hornby, T. George; Henderson, Christopher E.; Plawecki, Abbey; Lucas, Emily; Lotter, Jennifer; Holthus, Molly; Brazg, Gabrielle; Fahey, Meghan; Woodward, Jane; Ardestani, Marzieh; Roth, Elliot J.
Abstract : Background and Purpose—: The amount of task-specific stepping practice provided during rehabilitation poststroke can influence locomotor recovery and reflects one aspect of exercise dose that can affect the efficacy of specific interventions. Emerging data suggest that markedly increasing the intensity and variability of stepping practice may also be critical, although such strategies are discouraged during traditional rehabilitation. The goal of this study was to determine the individual and combined contributions of intensity and variability of stepping practice to improving walking speed and distance in individuals poststroke. Methods—: This phase 2, randomized, blinded assessor clinical trial was performed between May 2015 and November 2018. Individuals between 18 and 85 years old with hemiparesis poststroke of >6 months duration were recruited. Of the 152 individuals screened, 97 were randomly assigned to 1 of 3 training groups, with 90 completing >10 sessions. Interventions consisted of either high-intensity stepping (70%–80% heart rate reserve) of variable, difficult stepping tasks (high variable), high-intensity stepping performing only forward walking (high forward), and low-intensity stepping in variable contexts at 30% to 40% heart rate reserve (low variable). Participants received up to 30 sessions over 2 months, with testing at baseline, post-training, and a 3-month follow-up. Primary outcomes included walking speeds and timed distance, with secondary measures of dynamic balance, transfers, spatiotemporal kinematics, and metabolic measures. Results—: All walking gains were significantly greater following either high-intensity group versus low-variable training (all P <0.001) with significant correlations with stepping amount and rate ( r =0.48–60; P <0.01). Additional gains in spatiotemporal symmetry were observed with high-intensity training, and balance confidence increased only following high-variable training in individuals with severe impairments. Conclusions—: High-intensity stepping training resulted in greater improvements in walking ability and gait symmetry than low-intensity training in individuals with chronic stroke, with potential greater improvements in balance confidence. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02507466. Abstract : Supplemental Digital Content is available in the text.